Mithraic Studies (1975)
u.a. R. N. Frye, Mithra in Iranian History: 62-67 (theophoric names); A. D. H. Bivar, Religious Subjects on Achaemenid Seals: 90-105, Mithra and Mesopotamia: 275-289 (Nergal-cult and Mithra).